Plastic credit: A consortium blockchain-based plastic recyclability system. (15th February 2021) - Liu, Chao; Zhang, Xiaoshuai; Medda, Francesca
Abstract: By the end of 2015, approximately 6300 million tons (Mt) of plastic waste had been generated globally, but less than 10% of plastics was recycled. Since different types of plastics have various degrees of recyclability, consumer information about plastic product recyclability is paramount in order to increase the levels of plastic recycled. Against this context, the objective of this work is to define a plastic credit system to increase the amount of recyclable plastics. The plastic credit system assigns credit information to each plastic product and its corresponding company based on the percentage recyclability value of the plastic type and its composition. The methodology proposed is based on a unified and transparent credit system established by a double-chain system, which comprises a public blockchain CreditChain and a consortium blockchain M-InfoChain. The results show through the overall system performance analysis that the designed plastic credit system is capable of promoting a demand shift towards plastic products with higher plastic recyclability and achieving a lightweight operation for resource requirements and system maintenance.